Health Professionals' Views on Lifestyle Advice Delivery to Teenage and Young Adult Cancer Patients: A Qualitative Study. Issue 1 (January 2022) - Pugh, Gemma; Petrella, Anika; Pabary, Akshay; Cross, Aaron; Hough, Rachael; Soanes, Louise; Sabiston, Catherine; Fisher, Abigail
Abstract : Background: Many health professionals working with teenage and young adult cancer patients (TYA-HPs) do not provide advice on physical activity, dietary intake, smoking cessation, and alcohol consumption as part of routine cancer care. Objective: The aim of this study was to understand TYA-HPs' perspectives on the provision of health behavior advice and preferences on an intervention to help develop their health promotion skills. Methods: In-depth, semistructured interviews were conducted with 26 TYA-HPs (12 nurses, 8 clinicians, and 6 allied health professionals) whose average time working with teenage and young adult (TYA) cancer patients was 8 years. Each interview followed the same semistructured guide, which was based upon constructs of the COM-B model of behavior change (capability, physical opportunity, social opportunity, reflective motivation, and automatic motivation), transcribed verbatim, and analyzed using the Framework analysis. Results: Overall, TYA-HPs recognized the value and importance of promoting health behaviors but felt that their capability to provide health behavior advice was limited by the availability of, and access to, good-quality evidence linking health behavior to cancer outcomes. The TYA-HPs expressed confusion over professional responsibility to provide choices. Conclusions: The TYA-HPs recognize health behavior promotion to be a core part of TYA cancer care but feel ill-equipped to provide such advice to patients. Implications for practice: Mapped to constructs of the COM-B model of behavior, these findings suggest that TYA-HPs would benefit from cross–multidisciplinary team support for improved access to TYA-specific resources covering key health behaviors and skills-based training on delivering lifestyle advice. Abstract : Supplemental digital content is available in the text.